Продуктивність деревостанів Robinia pseudoacacia L. залежно від лісорослинних умов Придніпровського Степу України - Ситник, Свiтлана Анатолiiвна; Sitnik, Svitlana; Поліщук, Віталій Васильович; Поліщук, Vitaliy (Національний дендрологічний парк "Софіївка" НАН України, 2014)
Проаналізована вікова структура деревостанів Robinia pseudoacacia L. лісів Придніпровського Степу України,підпорядкованих Державному агентству лісових ресурсів України. Показано значний дисбаланс між площами, зайнятими віковими групами зі значним домінуванням перестиглої робінії. Досліджено продуктивність та її залежність від типу лісорослинних умов: з’ясовано залежність між запасом деревини та типом трофотопу і гігротопу. The age structure of stands of Robinia pseudoacacia L. forests of Pridneprovsk Steppe of Ukraine, that belong to the State agency forest resources of Ukraine was analyzed. A considerable disbalance between areas, which covered age groups with the considerable prevailing of overmature robinia was shown. The productivity of stands in the different types of trophotops and hyhrotops and its dependence on the type of forestry terms was investigated. The robinia arrives the maximal productivity in subor terms and the moist hyhrotop was established.
INFLUENCE OF FORESTLY TERMS OF PRIDNEPROVSK STEPPE OF UKRAINE ON THE PRODUCTIVITY OF STANDS OF ROBINIA PSEUDOACACIA L.
Keywords: вікова структура деревостанів Robinia pseudoacacia L; age structure of Robinia pseudoacacia stands L; трофотоп; trophotop; запас деревини; stock of wood